In vitro and intracellular antimycobacterial activity of a Bacillus pumilus strain - Hassi, Mohammed (2012)
Despite the declaration of tuberculosis (TB) as a global emergency by the world health organization (WHO) about 20 years ago, the worldwide problem of this disease has worsened due to increased drug resistance of tuberculosis bacilli and acquired immune deficiency syndrome (AIDS) pandemic. Consequently, fight against multidrug and extensively drug-resistant TB is a high priority for public health and research. The present work describes the isolation of a Bacillus pumilus strain secreting a metabolite of protein nature capable of inhibiting mycobacterial growth (Mycobacterium smegmatis, Mycobacterium aurum and Mycobacterium bovis BCG). This metabolite is not toxic, accumulates within the macrophage and inactivates the bacilli with a comparable efficiency to that of the pure commercial antimycobacterial substance Amikacin.